Exploring The Relationship Between Nutrition and Mental Health: A Systematic Review - Mei Lin Tan; Jasmine Teo; Daniel Wong (International Journal of Health and Medicine, 2024)
This systematic review examines the correlation between nutrition and mental health outcomes. By synthesizing data from various studies, the research highlights the impact of dietary patterns, micronutrient deficiencies, and food quality on mental health disorders, including depression and anxiety. The review underscores the importance of nutritional interventions in mental health care, suggesting that a balanced diet may play a crucial role in overall psychological well-being.